P049 Sleep Regularity is Associated with Stability of Daily Light Exposure in Adolescents During School and Vacation. (7th October 2021) - Hand, A; Stone, J; Shen, L; Vetter, C; Cain, S; Bei, B; Phillips, A
Abstract: Study Objectives: Light is the main time cue for the human circadian system. Irregular sleep/wake patterns are associated with poor health outcomes, which could be mediated by irregular patterns of light exposure. The relationship between sleep and light regularity has not been directly explored. We investigated the relationship between sleep and light regularity in adolescents, across school-term and vacation, using novel metrics for measuring light regularity. Methods: Daily sleep and light patterns were measured via wrist actigraphy in 104 adolescents (54% male, age M±SD = 17.17±0.80 years) over two weeks of school-term and a subsequent two-week vacation. The Sleep Regularity Index (SRI) was computed for each two-week block. Stability of daily light exposure was assessed using variation of mean daily light timing (MLiT), variation in daily photoperiod, and the Light Regularity Index. Associations between SRI and each light regularity metric were examined, and within-individual changes in metrics were examined between school and vacation. Results: More regular sleep was significantly associated with more regular scores for each light variability metric, during school and vacation. Between school and vacation sleep regularity decreased and nuanced changes in light patterns were observed. Variability measured by the MLiT variable increased, whereas variability measured by the LRI and photoperiod variable decreased. Conclusions: Adolescents with irregular sleep also have irregular patterns of light exposure. These findings suggest sleep regularity may be a useful proxy for variability in the main circadian time cue, meaning that irregular light exposure may carry implications for the developing adolescent circadian system.